Use of the Fix and Flap Approach to Complex Open Elbow Injury: The Role of the Free Anterolateral Thigh Flap - Christopher Hoe-Kong Chui; Chin-Ho Wong; Winston Y Chew; Mun-Hon Low; Bien-Keem Tan (Archives of Plastic Surgery, 2012)
Background Complex elbow injuries with associated nerve, muscle, or joint injury commonly develop post-inury stiffness. In order to preserve function, joint congruency, elbow stability and durable wound coverage must be achieved in a timely manner. Methods A retrospective review of patients who underwent orthopaedic fixation followed by free anterolateral thigh (ALT) flap soft tissue coverage was performed. Five patients were identified and included in this study. Results We present a series of 5 cases managed with this principle. Soft tissue defects ranged in size from 4×9 cm (36 cm2) to 15×30 cm (450 cm2) and were located either posteriorly (n=4) or anteriorly (n=1). Associated injuries included open fractures (n=3) and motor nerve transection (n=2). Wound coverage was achieved in a mean duration of 18.8 days (range, 11 to 42 day). There were no flap failures and no major complications. The mean postoperative active elbow motion was 102° (range, 45° to 140°). Conclusions In our small series we have highlighted the safety and utility of using the free ALT flap in complex elbow injuries. The ALT flap has many advantages which include abundant skin and subcutaneous tissue; vascularised vastus lateralis muscle that was used in our series to obliterate dead space, provide a vascular bed for nerve grafts and combat infection; and, access to fascia lata grafts for reconstruction of the triceps tendon.